2013
DOI: 10.1200/jco.2013.31.15_suppl.e20509
|View full text |Cite
|
Sign up to set email alerts
|

Role of prostaglandin pathways in radiotherapy-induced mucositis.

Abstract: e20509 Background: Pathways associated with proinflammatory molecules are upregulated in oral mucositis. Lalla (Support Care Cancer 18:95, 2010) found an association between mucositis pain scores, tissue COX-1, and salivary prostaglandins in 4 patients receiving dose-dense chemotherapy. We investigated whether similar changes would be seen with radiotherapy (XRT)-induced mucositis. Methods: Patients receiving XRT including the oropharynx were evaluated at 4 time points, before XRT, midway through XRT, end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Probably, prostaglandin E2 (PGE2) production, which is associated with ROS generation, is the most important product of COX-2 after exposure to radiation (Grunberg et al, 2013). The production of PGE2 is associated with oxidative DNA damage and genomic instability that may be prolonged for some days after exposure to radiation (Chai et al, 2012).…”
Section: Radiation-induced Normal Tissue Toxicity: Role Of Nf-κbmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably, prostaglandin E2 (PGE2) production, which is associated with ROS generation, is the most important product of COX-2 after exposure to radiation (Grunberg et al, 2013). The production of PGE2 is associated with oxidative DNA damage and genomic instability that may be prolonged for some days after exposure to radiation (Chai et al, 2012).…”
Section: Radiation-induced Normal Tissue Toxicity: Role Of Nf-κbmentioning
confidence: 99%
“…NF‐κB, via stimulation of COX‐2, regulates the release of prostaglandins in both irradiated and nonirradiated organs, through a phenomenon known as nontargeted effect (Chai et al, ). Probably, prostaglandin E2 (PGE2) production, which is associated with ROS generation, is the most important product of COX‐2 after exposure to radiation (Grunberg et al, ). The production of PGE2 is associated with oxidative DNA damage and genomic instability that may be prolonged for some days after exposure to radiation (Chai et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Saliva levels of various LM are more widely used for studying oral diseases than for systemic diseases. For example, patients with radiotherapy‐caused oral mucositis displayed higher saliva levels of PGD 2 , PGE 2 , and PGF 2 (Grunberg et al , ). Similarly, a different study found elevated levels of LTA 4 hydrolase in oral mucositis patients (Jehmlich et al , ).…”
Section: Lipid Mediators In Body Fluidsmentioning
confidence: 99%